A configuração da educação física no Instituto Federal de Educação, Ciencia e Tecnologia do Rio Grande do Norte IFRN: contexto e perspectivas atuais. - Souza Filho, Moyses de (2011)
Over time the Physical Education on IFRN has considered the sport as the only possibility of pedagogical action. In the purpose of investigating the aspects that determine this condition, this study aimed the context of physical education within the institutional framework and its current perspectives in the process of institutional transformation. In this sense, were addressed the following study questions: What political pedagogical aspects that influenced the context of Physical Education on IFRN and how the pedagogical experience on Mossoro s campus incorporated the perspectives of curricular proposals transformation for the High School and the theoretical changes of the Brazilian Physical Education. Methodologically the work was based on a qualitative approach characterized as a descriptive- comparative research. The technique of discourse analysis was employed in the speech of research collaborators having as categories of analysis the professional activities time in the institution; The ratio of official use of the assumptions to the pedagogical practice of Physical Education in IFRN; The sport in the education process of students and The Prospects of Physical Education in the current configuration of IFRN. The data analysis allowed us to infer that the theoretical methodology of pedagogical practice of Physical Education in IFRN need to be reformulated and that it is necessary a contextualization with the curricular principles of the political institutional pedagogical project and with the Curriculum Guidelines for Secondary Education. The teaching experience developed in the Mossoro s Campus was contextualized with the national curriculum guidelines for secondary education and the theoretical changes of the Brazilian Physical Education. We conclude that it is necessary a collective action of the group of teachers to transform the educational profile of Physical Education of IFRN, beyond the institutional support to be able to consolidate the physical education curriculum component in the current dimensions of society, human being, education, science, technology and work, proposed by the philosophical principles and epistemological political project of IFRN educational